PERAN OPINION LEADER SEBAGAI SUMBER INFORMASI POLITIK MASYARAKAT KABUPATEN MAMUJU TENGAH PADA PEMILIHAN KEPALA DAERAH TAHUN 2024 (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2025)
This study examines the role of opinion leaders as sources of political information during the 2024 Regional Head Election in Central Mamuju. Opinion leaders individuals with knowledge and influence function as intermediaries who filter and interpret political messages for the public. The research aims to (1) understand their role in informing the public, and (2) identify the factors influencing their candidate preferences. Using a qualitative descriptive method, data were collected through interviews, observation, and documentation, with triangulation ensuring validity. Findings show that opinion leaders significantly influence voters by conveying political information through social networks and interpreting mass media content, consistent with the Two-Step Flow theory. Their political preferences are shaped by candidates’ integrity, vision, communication skills, moral values, and support from political parties, although personal qualities are considered more decisive. These findings are expected to support the development of more effective political communication strategies for candidates and parties.